Comparison on aroma compounds in Chinese soy sauce and strong aroma type liquors by gas chromatography–olfactometry, chemical quantitative and odor activity values analysis - Wang, Xiaoxin; Fan, Wenlai; Xu, Yan (European food research & technology, 2014)
In order to elucidate the differences on aroma compounds in Chinese liquors with different aroma styles and the reasons, aroma compounds of Xijiu in soy sauce aroma and strong aroma type were investigated in the research. By gas chromatography–olfactometry (GC–O), aroma compounds in Chinese liquor were chosen for quantitative and odor activity value (OAV) analysis. Ethyl hexanoate, butanoic acid, 3-methylbutanoic acid, hexanoic acid and dimethyl trisulfide were considered to be the most powerful odorants in both liquor samples (aroma intensity ≥3.5) by GC–O. As important aroma compounds (OAV ≥10) in the liquors, ethyl propanoate, ethyl 2-methylpropanoate and 1-propanol were considered with much higher OAVs in soy sauce aroma type liquor, while OAVs of ethyl pentanoate, ethyl hexanoate, ethyl heptanoate, ethyl octanoate, ethyl lactate, hexyl acetate, butyl hexanoate, hexyl hexanoate and hexanoic acid were far lower in strong aroma type liquor. The OAV of ethyl hexanoate in strong aroma type liquor exceeded 50,000, which explained the reason why strong aroma liquor was considered with prominent fruity aroma. The odor differences between the liquors were mainly caused by the manufacturing practices.